2016
DOI: 10.1186/s12875-016-0566-0
|View full text |Cite
|
Sign up to set email alerts
|

Provider and patient perspectives on opioids and alternative treatments for managing chronic pain: a qualitative study

Abstract: BackgroundCurrent literature describes the limits and pitfalls of using opioid pharmacotherapy for chronic pain and the importance of identifying alternatives. The objective of this study was to identify the practical issues patients and providers face when accessing alternatives to opioids, and how multiple parties view these issues.MethodsQualitative data were gathered to evaluate the outcomes of acupuncture and chiropractic (A/C) services for chronic musculoskeletal pain (CMP) using structured interview gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 54 publications
1
67
1
Order By: Relevance
“…Additionally, primary care clinicians and patients have expressed difficulty in tapering long-term opioid use. [22][23][24] In this study, the transition of opioid prescribing to primary care occurred 3-6 months after surgery, and primary care continued to increase in percentage of opioid prescribing throughout the study period. Early and deliberate transition of care may be required for patients that continue to require opioids following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, primary care clinicians and patients have expressed difficulty in tapering long-term opioid use. [22][23][24] In this study, the transition of opioid prescribing to primary care occurred 3-6 months after surgery, and primary care continued to increase in percentage of opioid prescribing throughout the study period. Early and deliberate transition of care may be required for patients that continue to require opioids following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A review of stakeholder groups revealed several reasons for this, including rushed consultations and pain management having a low priority and being underresourced (Kress et al., ). Pain management, which should be multidimensional, often depend primarily on pharmacology, which in itself are presenting patients and the healthcare system with enormous challenges (Penney, Ritenbaugh, DeBar, Elder, & Deyo, ). Prescription for opioid medications for chronic pain has increased dramatically and is associated with increased opioid overdose, abuse and other harm in addition to uncertainty about long‐term effectiveness (Chou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…An Oregon survey revealed clinicians frequently feel they do not have nonmedication options for chronic pain patients, with concurrent belief that opioid medications are not effective for many patients. 27 Primary care clinicians did not consider acupuncture as a first line of care despite patients' perception that acupuncture was useful for short-term pain improvement. While some patients are resistant to acupuncture due to a fear of needles; one study found some patients are able to overcome their fear in their willingness to try anything for pain relief.…”
Section: The Need For Integrative Pain Management Educationmentioning
confidence: 99%